2007
DOI: 10.1002/ejlt.200600311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid supplements on ruminal biohydrogenation intermediates and muscle fatty acids in lambs

Abstract: The objective was to characterize the fatty acid (FA) composition of lamb meat with emphasis on biohydrogenation intermediates (BI) induced by dietary sunflower and linseed oil and to test if a synergistic effect on meat trans-11 18:1 and cis-9,trans-11 18:2 concentrations could be obtained with a blend of both oils. Thirty two lambs were assigned to four groups and fed for 6 weeks one of the following diets: pelleted dehydrated lucerne (Control); and Control supplemented with 7.4% of sunflower oil (SF), linse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
142
5
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 37 publications
17
142
5
4
Order By: Relevance
“…Recognized metabolites of 18:3n-3, including trienes (9c,11t,15c-18:3), dienes (11t,15c-18:2, 9c,13t-18:2 and 9c,15c-18:2), CLA (11t,13c-18:2, 11t,13t-18:2 and 12t,14t-18:2) and monoenes (13t-to 16t-18:1), were not different across finishing strategies. These rumen metabolites of PUFA were previously identified in a number of studies (Kraft et al, 2003;Cruz-Hernandez et al, 2004 andDestaillats et al, 2005;Bessa et al, 2007;Gomez-Cortes et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…Recognized metabolites of 18:3n-3, including trienes (9c,11t,15c-18:3), dienes (11t,15c-18:2, 9c,13t-18:2 and 9c,15c-18:2), CLA (11t,13c-18:2, 11t,13t-18:2 and 12t,14t-18:2) and monoenes (13t-to 16t-18:1), were not different across finishing strategies. These rumen metabolites of PUFA were previously identified in a number of studies (Kraft et al, 2003;Cruz-Hernandez et al, 2004 andDestaillats et al, 2005;Bessa et al, 2007;Gomez-Cortes et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…The lipid sources used in the present experiment were supplied at 30 g/kg DM. A preliminary feeding experiment indicated that roughage (maize silage) intake was reduced when soybean oil was supplied at 50 g/kg DM, Fatty acid profile in the RF and adipose tissue of ruminants is influenced by the addition of lipids to the diet (Bessa et al, 2007;Shingfield et al, 2011), or the addition of supplements high in lipids (e.g. algae; Or-Rashid et al, 2008;Boeckaert et al, 2008), or the inclusion of whole cottonseed and soybean to the diet (Mohamed et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid (FA) profile in the rumen fluid (RF) or adipose tissue of ruminant is influenced by the addition of oils in the diet, such as sunflower oil (Bessa et al, 2007), safflower oil (O'Kelly and Spiers, 1991), fish oil (Kim et al, 2008) and linseed oil (Shingfield et al, 2011). The common objectives in most studies using addition of FA in the diet, is to decrease saturated and trans FAs and increase conjugated linoleic acid (CLA)s, 18:3n-3, 20:5n-3, and 22:6n-3.…”
Section: Introductionmentioning
confidence: 99%
“…Trans 18:1 isomers are quantitatively the most important in ruminant meat and milk fat. Although numerous isomers with double bonds in positions D4 to D16 are present, trans-11 18:1 is typically the most abundant in milk and meat of grazing ruminants or on diets containing high proportions of grass silage or ensiled forage legumes (Nuernberg et al, 2005;Bessa et al, 2007;Vanhatalo et al, 2007; Table 8). Concentrations of trans-18:1 are higher in milk from pasture compared with conserved forages (Table 3) and tend to be increased on high-concentrate diets (Chilliard et al, 2007; Table 4).…”
Section: Tfa Content Of Ruminant-derived Foodsmentioning
confidence: 99%
“…In several studies, linseeds also lowered the proportion of 16:0 in IMF (Noci et al, 2007a;Herdmann et al, 2010a;Nassu et al, 2011). Dietary supplements of oils and oilseeds enriched in 18:3n-3 induce similar changes in muscle fatty acid composition of growing lambs (Bessa et al, 2007;Sinclair, 2007;Turner et al, 2012a). A number of studies have examined the potential of feeding concentrates containing fish oil or marine algae to enrich 20:5n-3 and 22:6n-3 in muscle of growing cattle and lambs.…”
mentioning
confidence: 99%